‘Strengthening procurement governance in Bangladesh: A review of the Local Government Engineering Department's role in ensuring accountability and efficiency - Hossain, Md. Kamal (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2024.